Compendium of hydrogen energy. Vol. 2, Hydrogen storage, distribution and infrastructure - Gupta, Ram.; Basile, Angelo (Angelo Bruno); Veziroglu, T. Nejat (Burlington, United Kingdom : Woodhead Publishing, 2015)
Compendium of Hydrogen Energy, Volume 2: Hydrogen Storage, Distribution and Infrastructure focuses on the storage and transmission of hydrogen. As many experts believe the hydrogen economy will, at some point, replace the fossil fuel economy as the primary source of the world's energy, this book details hydrogen storage in pure form, including chapters on hydrogen liquefaction, slush production, as well as underground and pipeline storage. Other sections in the book explore physical and chemical storage, including environmentally sustainable methods of hydrogen production from water, with.
''3.7.1. Nucleate pool boiling heat transfer to slush and liquid hydrogen''''3.8. Conclusions'';''3.9. Future trends'';''3.10. Sources of future information and advice'';''Appendix A. Production'';''Appendix B. Flow and heat transfer'';''Appendix C. Measurement instrumentation'';''References'';''Chapter 4: Underground and pipeline hydrogen storage'';''4.1. Underground hydrogen storage as an element of energy cycle'';''4.1.1. Industrial needs in underground hydrogen storage (UHS)'';''4.1.2. Conversion of hydrogen into other forms of energy and vice versa''
Print version record.
Elsevier
Keywords: Hydrogen as fuel; Hydrogen as fuel; TECHNOLOGY & ENGINEERING / Power Resources / General; Electronic books